The Influence of Digital Marketing and Product Quality on Purchasing Decisions for Skincare Skintific Products for members of GenBi Lampung Province - Ali, Sopian; Habiburachman (STIE Ekuitas, 2025)
Introduction/Main Objective: This paper discusses the influence of digital marketing and product quality on purchasing decisions for Skintific skincare products among Gen-BI members in Lampung Province. In today’s digital era, effective marketing strategies are essential to attract consumers, especially the younger generation who are connected to technology. Background Problems: This study examines how digital marketing and product quality influence purchasing decisions for skincare, posing the research question: